Parâmetros produtivos e adaptabilidade e estabilidade temporal de genótipos experimentais de batata-doce de polpa branca e creme na região Oeste Paulista - Garcia Neto, Jair (2022)
West Paulista is the main sweet potato producing region in the state of São Paulo, but it has low productivity and low quality of roots, mainly due to the use of obsolete, degenerate genotypes that are susceptible to pests and diseases. In this region, despite the considerable economic and social relevance of the culture, the same genotypes 'Ligeirinha Paulista', 'INIA Arapey' and 'Canadense' have been used for over a decade. To strengthen sweet potato cultivation in the region, it is important to develop new genotypes with productive potential. Considering the above information, the objective was to select experimental genotypes of sweet potato with white and cream pulp in terms of production parameters, adaptability and phenotypic stability in six growing seasons, in order to obtain plants that meet the needs of producers in the West Paulista region and the national demand. The experiments were installed in six seasons: 06/05/2020 (autumn – winter); 10/09/2020 (spring - summer); 12/10/2020 (spring – summer – autumn); 01/29/2021 (summer – autumn); 04/23/2021 (autumn - winter); and 05/20/2021 (autumn – winter – spring), evaluating 18 experimental sweet potato genotypes recently developed by the Centro de Estudos em Olericultura e Fruticultura do Oeste Paulista and the controls 'INIA Arapey', 'Ligeirinha Paulista' and 'UZBD 06' (Canadian standard). Parameter’s indicative of productivity and quality of commercial roots were evaluated. The analysis of phenotypic stability and adaptability was carried out according to the methodology of Eberhart & Russell (1966) and by the centroid method, using the Genes program. The UZBD-C-06, UZBD-K-39 and UZBD-K-55 genotypes had better agronomic performance than the controls, being promising for cultivation in the West Paulista region. Based on the Centroid methodology, it is recommended to use the genotypes UZBD-C-06, UZBD-K-39 and UZBD-K-55, which have high general adaptability, were less influenced by environmental variation and can be cultivated in all seasons. The method described by Eberhart and Russell (1966) recommends the genotypes UZBD-L1-04, UZBD-L1-17, UZBD-L2-19, UZBD-L3-20, UZBD-L3-50, UZBD-L4-46, UZBD-L5-08, UZBD-C-06, UZBD-K-39 and UZBD-K-55 to be cultivated in favorable environments, which can respond positively to environmental improvements. The methodologies complement each other and increase the reliability in the recommendation of genotypes.